Ritualidad en la sanación de las enfermedades culturales de la población de San Lucas en la ruta del Qhapaq Nañ - Abad Macas, Stefany Viviana (2020)
Since the beginning the human being has maintained a coexistence with nature solving problems of food, living place, health through resources that it offers as plants. There is a wealth of knowledge about perception and health preservation that are cataloged as ancestral knowledge and used by populations for maintaining or restore people´s well-being. This practice covers an important social anthropologic category as rituality that are cultural practices of ancestral knowledge with a close relation with the magical and religious. This research focuses on this aspect which was carried out in San Lucas parish having like objective describe the rituality used in the healing of cultural diseases of this population. This is a mixed focus study with a descriptive design and cross section and ethnographic. The quantitative component was investigated by reviewing published documents with the help of bibliographic records and this determined that there are 4673 inhabitants, most were women (52,71%), majority age group 15 to 64 years with 52,57%, the 80,50 % are indigenous inhabitants, 8,12 % illiteracy, 41,60 % of economically active population dedicating the majority to primary activities. The qualitative part of the research was carried out through interviews which were applied to 6 Traditional Health Agents (THA) gettingas results that the main rituals are the cleaning with plants, blows, diagnosis through urine, cleaning with egg, washing and cleaning home, and t-he main plants used for the rituals are rue, marco, rosemary, laurel and santa maría. Key words: Ancestral wisdom, ceremony-ritual, pre-inca road